The inside out stroke in men´s tennis: Strategies and tactics - Martin, E.; Campos, J.; Crespo, M. (Coaching and Sport Science Review, 2018)
Understanding the strategy and tactics in tennis will help to make decisions when preparing a match against a certain opponent, depending on the different aspects of tennis performance, on the basis of the indicators of sport performance (efficiency, accuracy, technical command...). In line with the direction and their intention, players will use a certain technical movement for greater effectiveness and to increase the possibilities of success. In tennis, the inside out forehand provides a new possibility in the set of tactical and strategic variables. This article presents some ideas on the strategies and tactics of the inside out forehand, as well as several examples for its on-court training.